Optimization of Humanistic Education in the Integrated Islamic Primary School - Asep Kurniawan (UIN Siber Syekh Nurjati Cirebon, 2019)
AbstractOnly a few primary schools apply humanistic education. This could be viewed from the students’ moral decadence and the process of dehumanizing education. Even though there are some primary schools implement humanistic education,their application is not maximized. The purpose of the research was to reveal in depth the efforts of Integrated Islamic primary school Sabilul Huda in maximizing humanistic education. This research is a case study of descriptive qualitative. The instruments of data collection are in-depth observation, in-depth interviews, and documentation. Data analysis was conduted conducted through collecting data, reducing data, displaying data, and conclusing data. The research results showed that Integrated Islamic primary school Sabilul Huda maximized humanistic education through applying the principles of humanistic education. It was indicated by the creation of learning conditions through the application of the principles of effective learning. Students contributed actively in finding and processing teaching materials. School viewed students as unique and intelligent individuals. The effort to maximize humanistic education has showed good result, if it was reviewed on academic and non-academic achievements, and students’ character. This is indicated by ideal academic scores, achievements in various competitions of interest,talents, and students' good behavior.Keywords: appreciation, uniqueness, joyful, achievement, moralityAbstrakTidak terlalu banyak sekolah dasar yang menyelenggarakan pendidikan humanistik. Hal ini dapat terlihat dari dekadensi moral para pelajar dan proses dehumanisasi pendidikan. Kalaupun ada, penerapannya belum maksimal. Tujuan penelitian ini adalah untuk mengungkap secara mendalam upaya SDIT Sabilul Huda dalam memaksimalkan pendidikan humanistik. Jenis penelitian ini adalah kualitatif deskriptif studi kasus. Instrumen pengumpulan data ialah observasi mendalam, wawancara mendalam, dan dokumentasi. Teknis analisis data dilakukan melalui pengumpulan data, reduksi data, display data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa SDIT Sabilul Huda sudah berupaya memaksimalkan pendidikan humanistik melalui penciptaan kondisi belajar yang menerapkan prinsip-prinsip pendidikan humanistik. Hal ini ditunjukkan dengan penciptaan kondisi belajar melalui penerapan prinsip-prinsip pembelajaran efektif. Siswa berkontribusi aktif dalam mencari dan mengolah materi ajar yang didapatkan. Sekolah memposisikan siswa sebagai individu yang unik dan anggapan bahwa setiap siswa adalah cerdas. Upaya memaksimalkan pendidikan humanistik sudah memperlihatkan hasil yang cukup baik pada sisi prestasi siswa baik akademik maupun non akademik serta karakter siswa. Hal ini ditunjukkan dengan skor akademik yang ideal, prestasi di berbagai lomba minat, bakat, dan perilaku baik siswa.Kata kunci: apresiasi, keunikan, suasana menyenangkan, prestasi, moral